Deficits in sentence expression in amyotrophic lateral sclerosis. Issue 1 (March 2015) - Ash, Sharon; Olm, Christopher; McMillan, Corey T.; Boller, Ashley; Irwin, David J.; McCluskey, Leo; Elman, Lauren; Grossman, Murray
Abstract: Quantitative examinations of speech production in amyotrophic lateral sclerosis (ALS) are rare. To identify language features minimally confounded by a motor disorder, we investigated linguistic and motor sources of impaired sentence expression in ALS, and we related deficits to gray matter (GM) and white matter (WM) MRI abnormalities. We analyzed a semi-structured speech sample in 26 ALS patients and 19 healthy seniors for motor- and language-related deficits. Regression analyses related grammaticality to GM atrophy and reduced WM fractional anisotropy (FA). Results demonstrated that ALS patients were impaired relative to controls on quantity of speech, speech rate, speech articulation errors, and grammaticality. Speech rate and articulation errors were related to the patients' motor impairment, while grammatical difficulty was independent of motor difficulty. This was confirmed in subgroups without dysarthria and without executive deficits. Regressions related grammatical expression to GM atrophy in left inferior frontal and anterior temporal regions and to reduced FA in superior longitudinal and inferior frontal-occipital fasciculi. In conclusion, patients with ALS exhibit multifactorial deficits in sentence expression. They demonstrate a deficit in grammatical expression that is independent of their motor disorder. Impaired grammatical expression is related to disease in a network of brain regions associated with syntactic processing.